PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII MTsN 7 AGAM - Jelia, Yossi (Departemen Matematika, 2023)
The key to success for pupils in mathematics is their ability to solve problems. to think carefully and critically in the field of mathematics studies and daily routine. The ability of class VIII MTsN 7 Agam students to understand, develop strategies, solve and re-examine problems are poor. This problem that arises is overcome with the Discovery Learning learning model, through quasi-experimentation and Design of Randomized Posttest-Only Control Group. The instance classes were taken using a simple random method to obtain experimental class VIII 6 and control class VIII 7. The tests were examined using the t test, with P-Value at zero indicates the Discovery Learning model is better at improving mathematical problem solving compared to direct learning in class VIII MTsN 7 Agam.Keywords – Discovery learning, Mathematical Problem Solving Abilitie